The Influence of Junior High School Students’ Self Confidence on Their Speaking Ability - mar'atus syarifah; Nuzul Isna (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The objective of this study is to find out the correlation between students’ self-confidence and their speaking ability. This study was conducted at a senior high school at Aceh Barat Daya. The method is a correlation research method using Product Moment Correlation. The total number of research subjects is 54 students. The result of this study showed that there is a correlation between students’ self-confidence and their speaking ability as the significance value is 0.00 and lower than 0,05. The correlation is indicated as in extremely weak correlation because the value of R2 is 0,106. It can be suggested that the students should improve their self-confidence and have good achievement in speaking.